To Post or Not to Post? Factors Influencing State FFA Officers’ Social Media Behaviors - Tiffany Rogers-Randolph; Lisa K Lundy; Ricky W Telg; Joy N Rumble; Brian Myers; Angela B. Lindsey (Journal of Applied Communications, 2021)
The demand for agriculture, food, and natural resource (AFNR) messages to be conveyed via channels of social media provides a natural inclination to seek out digital natives, such as state FFA officers, to fill the present gap of agriculturalists in online environments. The purpose of this study was to examine the factors that influence state FFA officers’ behaviors of communicating about AFNR issues on social networking sites. The theoretical framework that guided this study of communication behaviors was the theory of planned behavior. A census of the accessible population of 276 state officers was attempted, and 97 usable responses were received (35.1%). The findings reinforced the use of the theory of planned behavior to understand, predict, and change AFNR social media behaviors. The significance of subjective norms suggested that online AFNR communication is mainly under subjective control for state FFA officers. To increase online engagement of state FFA officers, it is recommended that behavioral change efforts target normative beliefs and that clear behavioral expectations are expressed. Further research is recommended to determine if the significance of subjective norms as a predictor of intent is unique to technological and social media behaviors or applicable to a broader context. Additional research with other populations of young agriculturalists is also recommended.
Keywords: theory of planned behavior; social networking sites; communication behaviors; state FFA officers; agriculture; food; and natural resource issues